PENGARUH KOMPLEKSITAS TUGAS, SELF-EFFICACY, DAN PENGALAMAN AUDIT TERHADAP AUDIT JUDGEMENT (STUDI PADA AUDITOR BPK RI PERWAKILAN PROVINSI ACEH) - Maghfirah, Indah; Yahya, M Rizal (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
The purpose of this research is to determine the influence of activity ratio, systematic risk, and outside ownership to Internet Fianancial Reoprting in manufacture companies sectors of the consumer goods industry listed in Indonesia Stock Exchange (BEI) during 2011 until 2015. The method used in this research is simple random sampling method. The sample of this research is manufacture companies sectors of the consumer goods industry listed in Indonesia Stock Exchange during 2011 until 2015. A total of 24 manufacturer companies are used as samples in this study. The analysis method used in the research is logistic regression analysis. The result of this research shows that (1) the simultaneous of activity ratio, systematic risk, and outside ownership has significant effect on Internet Financial Reporting (2) activity ratio has significant effect on Internet Financial Reporting (3) systematic risk has no significant effect on Internet Financial Reporting (4) outside ownership has significant effect on Internet Financial Reporting